Assessment of dietary nitrate supplementation: prevalence of use, knowledge, attitudes and beliefs among active Australians - McMahon, Nicholas F.; Brooker, Paige G.; Pavey, Toby; Leveritt, Michael D. (Frontiers in Nutrition, 2023)
Use of nitrate as a dietary supplement has gained popularity amongst athletes and recreationally active individuals to enhance exercise performance. However, the prevalence and patterns of use, and knowledge of nitrate as a dietary supplement are unknown. Individuals (≥16y) completed a 42-item online questionnaire to collect (i) sociodemographic information; (ii) participation in activity and sport; (iii) nitrate supplementation use and reasons; (iv) attitudes and beliefs regarding information sources and the safety of nitrate as a dietary supplement; and(v) knowledge of dietary nitrate supplements. In total, 1,404 active adults (66% female) took part in the study. Only about one in ten respondents (11.9%) reported they had consumed dietary nitrate ('users') in the past, most commonly as beetroot juice (31.3%). Over two-thirds (69.4%) of users could not correctly identify the correct timing of intake relative to performance time to best improve exercise performance, and most users (82.3%) were unsure of the contraindications to oral consumption of dietary nitrate supplements. Only 3.9% of users experienced adverse effects after ingesting dietary nitrate supplements. Among non-users, Tthe most common reasons respondents selected for not using supplementing their diet with dietary nitrate supplements were 'I don't think I need to' (70.2%) and 'I have never thought about it' (69.2%). Over two-thirds (69.4%) of users could not correctly identify the correct timing of intake relative to performance time to best improve exercise performance, and most users (82.3%) were unsure of the contraindications to oral consumption of dietary nitrate supplements. Only 3.9% of users experienced adverse effects after ingesting dietary nitrate supplements. There is evidence to support the efficacy of dietary nitrate intake in improving exercise performance. However, findings from this study suggest dietary nitrate is underutilised. Educational messages that target dietary nitrate consumption should be targeted towards nutritionists, coaches, and exercise physiologists to bridge the gap between knowledge-to-practice.